Use of anatomically-accurate 3-dimensional nasal airway models of adult human subjects in a novel methodology to identify and evaluate the internal nasal valve - Hosseini, Sana; Schuman, Theodore A.; Walenga, Ross; Wilkins, John V.; Babiskin, Andrew; Golshahi, Laleh (Computers in biology and medicine, 2020)
The optimal method for radiographic evaluation of the internal nasal valve (INV) has not been established. The objective of this study was to develop a method to assess the cross-sectional area and the angle of the INV using anatomically-accurate 3D digital nasal airway models. Axial CT images of the paranasal sinuses of twenty adult subjects with healthy nasal airways (50% female and 50% age ≥ 50) were used to create the models. Patients with significant radiographic evidence of sinonasal disease were excluded. A primary cutting plane that passed through the edge of the nasal bone, upper lateral cartilage, and the head of the inferior turbinate was defined in coronal view. This primary coronal cutting plane was then rotated in 5° increments anteriorly while ensuring the anatomic criteria for the INV were still met. The cutting plane resulting in the minimum INV area was identified as the optimal cutting plane and the total cross-sectional area of INV in this plane,198.79 ± 54.57 mm2, was significantly less than the areas obtained using the existing methods for radiographic evaluation of the INV. The angle between the optimal cutting plane and nasal dorsum was 75.00 ± 10.26°, and the corresponding INV angle was 10.77 ± 6.02°.